Laboratory Evaluation of Toxicity of Registered Pesticides to Adult Amblyseius addoensis (Van der Merwe & Ryke) (Acari: Phytoseiidae) - Schwartz, A. (South African Journal of Enology and Viticulture, 2017)
The toxicity of 23 registered vineyard pesticides to the predaceous mite, Amblyseius addoensis (Van der Merwe & Ryke), were examined in the laboratory to obtain information on how to protect this important natural enemy of Tetranychus urticae Koch in an integrated pest-management programme. Methods of handling and testing the mites are described. Test results on adult A. addoensis are presented. The majority of the insecticides and acaricides were highly toxic, with the fungicides being neutral to moderate in effect. It is recommended that pesticides with a high toxic rating be subjected to field testing before final decisions are made.